Techniques Of Fake News Detection - Garg, Harshit; Joshi, Ankita (Journal of Advanced Research in Instrumentation and Control Engineering, 2020)
Fake news is the contents that claim people to believe with the falsification, sometime it is the sensitive messages. Mixing both believable and unbelievable information on social media has made the confusion of truth. That is the truth will be hardly classified. The techniques for detecting the Fake News means its a false story which comes from unauthorized source. Only by building a model based on a count vectorizer or a Term Frequency- Inverse Document Frequency i.e. TF-IDF score matrix calculation can only get you so far. It may happen that the meaning two article be similar. Combating the fake news is a classic text classification project with a straight forward proposition. We can implement a task by Naïve Bayes or any other method to find out the real vs fake news. How to cite this article: Garg H, Goyal A, Joshi A. Techniques of Fake News Detection. J Adv Res Instru Control Engg 2020; 7(2): 8-11.